Humerus trochlear angle (HTa)—a possible alternative for Baumann angle in the reduction of supracondylar humerus fractures - Gang Chen (BMC, 2021)
Abstract Background The supracondylar humerus fractures are the most common fracture in children’s elbows. Generally, close reduction and percutaneous pinning can provide satisfactory outcomes after adequate reduction. Baumann angle is commonly used to evaluate reduction quality, however, it may fail to assess reduction well when the elbow is in flexion and/or when the patient is young. We conducted this study to evaluate the potential value of the humerus trochlear angle (HTa) for the reduction evaluation and compare it with the Baumann angle. Methods We retrospectively reviewed supracondylar humerus fractures in our trauma center from 2016 to 2019. Patients were grouped as followed: in the HTa group, an arthrogram was used to evaluate the HTa angle and reduction (HTa, defined by the intersection of the axis of the humerus shaft and the tangent of the articular surface of the trochlear); In the Baumann group, the Baumann angle was used to assess the reduction. Baumann angle ratio (BA of injured side/BA of contralateral side) was calculated to evaluate the reduction quality between groups. Flynn’s grading criteria were utilized to evaluate both function and cosmetic outcomes in two groups during the follow-up. Operation time, fluoroscopy shots, complications and Flynn’s grading scores were compared between groups. Results A total of 57 patients with an average age of 4.62 years and follow-up duration of 21.49 ± 5.40 months were included in the analysis. The gender and age distributions were similar in the two groups. Fluoroscopy shots in the HTa group were significantly less than in Baumann group (16.17 ± 0.73 vs. 21.85 ± 0.78, p < 0.0001), and operation time were also less in HTa group (45.78 ± 1.96 min vs. 62.21 ± 1.58 min, p < 0.0001). Baumann ratio showed no significant difference between the two groups (1.002 ± 0.023 in the Baumann group and 1.01 ± 0.023 in HTa group, p < 0.0001). Length of hospitalization, complications, and Flynn’s grading scores were similar between groups. The HTa angle was positively correlated with Baumann angle in the HTa group (R-value is 0.71 and P = 0.0002). Conclusions There was no significant difference in reduction quality and Flynn’s scores between HTa and Baumann groups. Furthermore, HTa was associated with shorter operation time and less radiation exposure in this investigation. Therefore, HTa may be a convenient and reliable parameter that could guide the reduction of supracondylar humerus fractures, especially for young children.